KEJADIAN KAWIN BERULANG PADA SAPI POTONG BETINA PERANAKAN LIMOSIN DAN SIMENTAL DI KECAMATAN WONOSALAM KABUPATEN JOMBANG PERIODE 2015 - 2018 - Subagio, Muharam; Triana, Indah Norma; Poernomo, Bambang; Wurlina, Wurlina; Srianto, Pudji; Utomo, Budi (Journal of Basic Medical Veterinary, 2019)
Repeat Breeding is an adult cattle which have normal estrous cycle and clear signs of estrous but did not get pregnant when it got breed by natural mating or artificial insemination. The main purposes of this study is to know the number of repeat breeding cases in beef cattle in regency Jombang period of 2015-2018. The metode of the study is survey which collected by recording and survey. Were analyzed though Normality Test (Kolmogorov-Smirnov Test) and Homogenity Test and followed by T Test. Questionnaire test result processed using Kendall's Tau-b Correlation Test. Study result showed that repeat breeding cases fluctuate significantly per year and the factors affecting fertilization failure and early embrionic death, hormonal, infection, and management factors.